Islamic Green Banking At Bank Pembangunan Daerah In Indonesia - Rahmayati, Rahmayati; Mujiatun, Siti; Sari, Maya (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
This research aims to prove the concept of Islamic Green Banking in the banking system in Indonesia, precisely at the Bank Pembangunan Daerah (BPD) bank and to proves that CSR, Green Accounting, Growth Financing, NPF, Liability on Green Banking have a simultaneous and partial test effect on Green Banking. The research method used is descriptive quantitative, using secondary data from the bank's Annual Report from 2015-2020 at PT. BPD Aceh Syariah, PT. BPD Sumatera Utara, PT. BPD Jambi, PT. BPD. Nagari, PT. BPD. Riau and Kepulauan Riau, PT. BPD Sumatera Selatan and Bangka Belitung. The results of the study prove that the Corporate Social Responsibility (CSR), Growth Financing, Green Accounting, NPF variable have an effect on Green Banking except for Liability variable which shown negative result on Green Banking and this study is that the application of Green Banking is a pattern that can be implemented by the BPD through digitizing online services.